Improvement of Split Skin Graft Quality Using a Newly Developed Collagen Scaffold as an Underlayment in Full Thickness Wounds in a Rat Model. Issue 5 (November 2015) - Held, Manuel; Medved, Fabian; Stahl, Stéphane; Bösch, Cedric; Rahmanian-Schwarz, Afshin; Schaller, Hans-Eberhard
Abstract : Introduction: Frequently, full thickness skin defects were treated through split skin graft (SSG) transplantation. However, this is usually associated with a reduction of skin quality and scarring. In this context, a newly developed collagen cell carrier (CCC) has been evaluated as an underlayment in SSG transplantations in a rat model. Materials and Methods: Twenty-eight standardized full thickness skin defects were generated on the back of 28 adult male Lewis rats. The wounds were randomized and treated with SSG transplantation solitarily (n = 14) or SSG transplantation using CCC as an underlayment (n = 14). For skin quality analysis, a histological evaluation was performed 3 months postoperative in regard to epidermal cell count and epidermal and dermal thickness. Results: Wounds treated with SSG and CCC demonstrated a thicker epidermis and significantly higher epidermal cell count compared to SSG solitarily. At the time of evaluation, epidermal thickness of SSG and CCC was comparable to untreated, healthy skin (no statistically significant differences). Discussion: As split skin grafting is frequently associated with skin quality reduction, the presented results reveal the beneficial effects of CCC in terms of skin graft quality improvement. This may offer unique opportunities in wound management and encourages further evaluation of CCC in surgical applications and regenerative medicine.